Security of multimedia in the web - Zeki, Akram M. (IIUM Press, 2011)

(untitled)
The use of data hiding, as a viable fonn of communication, has been largely propelled by the growth of the Internet. The Internet offers an opportunity to exchange large amounts of digital infonnation over great distances. The prevalence of media, such as audio, videos, and images, on the Internet provides an ideal channel for data hiding communication.Voice over Internet Protocol (VOIP) became a natural target for data hiding, it is appropriate to enable hidden communication throughout Internet Protocol (IP) networks.nVoIP data hidingcovers a wide range of information hiding techniques; including popular techniques based on IP.This paper istrying to discover some of the data hiding applications and techniques over internet.